Control of vibration using compliant actuators - Mareta, Sannia; Halim, Dunant; Popov, Atanas A. (American Society of Mechanical Engineers, 2017)
This work proposes a method for controlling vibration using compliant-based actuators. The compliant actuator combines a conventional actuator with elastic elements in a series configuration. The benefits of compliant actuators for vibration control applications, demonstrated in this work, are twofold: (i) vibration reduction over a wide frequency bandwidth by passive control means; (ii) improvement of vibration control performance when active control is applied using the compliant actuator. The vibration control performance is compared with the control performance achieved using the well-known vibration absorber and conventional rigid actuator systems. The performance comparison showed that the compliant actuator provided a better flexibility in achieving vibration control over a certain frequency bandwidth. The passive and active control characteristics of the compliant actuator are investigated, which shows that the control performance is highly dependent on the compliant stiffness parameter. The active control characteristics are analyzed by using the Proportional and Derivative (PD) control strategy which demonstrated the capability of effectively changing the respective effective stiffness and damping of the system. These attractive dual passive-active control characteristics are therefore advantageous for achieving an effective vibration control system, particularly for controlling the vibration over a specific wide frequency bandwidth.